Fighting obesity: non-pharmacological interventions - Higuera-Hernández, María Fernanda (2018)
The abnormal or excessive fat accumulation that impairs health is one of the criteria that fulfills obesity. According to epidemiological data, obesity has become a worldwide public health problem that in turn would trigger additional pathologies such as cardiorespiratory dysfunctions, cancer, gastrointestinal disturbances, depression, sleep disorders, just to mention a few.